UV hardening liquid as well as preparation method and application thereof

By introducing modified polyether polyols, terminal hydroxyl polyolefins and fluorocarbon alcohol monomers into the UV hardening liquid, the problem that UV hardening liquid in the prior art is difficult to take into account both stain resistance and acid and alkali resistance, and better surface protection effect is achieved.

CN119859466AActive Publication Date: 2025-04-22DONGGUAN AOZON ELECTRONICS MATERIAL +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510096763.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In the prior art, it is difficult to develop a UV hardening liquid that has excellent stain resistance and certain acid and alkali corrosion resistance, which affects the effective protection of the surface of electronic products.

Method used

By introducing modified polyether polyols, terminal hydroxyl polyolefins and fluorocarbon alcohol monomers with long chain structures, the stain resistance and acid and alkali resistance of the cured film formed by the UV hardening liquid are improved.

Benefits of technology

It effectively improves the stain resistance and acid and alkali resistance of UV hardened liquid cured film, and enhances the protection effect on the surface of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253578270000131
    Figure BDA0005253578270000131
  • Figure BDA0005253578270000141
    Figure BDA0005253578270000141
Patent Text Reader

Abstract

The invention provides UV hardening liquid as well as a preparation method and application thereof. The UV hardening liquid comprises a main agent and a photoinitiator, the main agent is prepared from the following raw materials in parts by weight: 5 to 15 parts of modified polyether polyol or modified polyester polyol, 5 to 10 parts of hydroxyl-terminated polyolefin and 0.25 to 0.35 part of fluorocarbon alcohol monomer; the modified polyether polyol or the modified polyester polyol contains at least one of a cardanol structural unit and a cardol structural unit. The modified polyether polyol with a long-chain structure, the hydroxyl-terminated polyolefin and the fluorocarbon alcohol monomer are introduced into the UV hardening liquid, so that the stain resistance and the acid and alkali resistance of a cured film formed by the UV hardening liquid can be effectively improved, and the protection effect on the surfaces of related products such as electronic products can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glue, and in particular relates to a UV curing liquid and a preparation method and application thereof. Background Art

[0002] During the preparation and use of 3C products (such as mobile phones, smart watches and tablets, etc.), the surface needs to be protected. PET film has good light transmittance and mechanical properties and is widely used. To prevent the PET surface from being scratched, the most common method is to apply a layer of hardening liquid on its surface to improve its scratch resistance. Some products even require it to have certain stain resistance (low surface tension, not easy to stick to pollutants) and acid and alkali resistance during its manufacturing process. UV hardening liquid has fast curing speed, fast film forming speed, and excellent scratch resistance. It is widely used in vacuum coating, PVC flooring, car clothing hardening coating, car headlights, and kitchenware panels. Therefore, applying a layer of UV hardening liquid as a protective coating on the PET substrate also has broad application prospects.

[0003] Patent CN112980318A uses nano-alumina modified polyurethane acrylic resin oligomer, fluorine-modified polyurethane acrylate oligomer, photoinitiator, polytetrafluoroethylene micro-powder wax, modified polyurethane dispersant and ether, ester diluent to prepare a highly wear-resistant and fingerprint-resistant matte UV curing liquid. Although it has excellent wear resistance and stain resistance, its main UV resin has high functionality and a molecular weight of only about 1000-2500. Although the cured coating has a certain acid and alkali corrosion resistance, it has a high shrinkage rate and is easy to wrinkle, affecting the appearance. Patent CN110606912A made a homemade acrylic resin, introduced fluorine elements, and added photoinitiators and other additives to prepare a UV curing liquid that meets the hardness and wear resistance requirements while also having anti-fingerprint and stain resistance effects, but its acid and alkali resistance is poor.

[0004] Therefore, in the current prior art, there are few reports on the relevant technology of UV curing liquid that has both excellent stain resistance and certain acid and alkali corrosion resistance. Therefore, developing a UV curing liquid that has both good stain resistance and good acid and alkali resistance is of great significance for further improving its protective effect on the surface of related products such as electronic products. Summary of the invention

[0005] In order to solve the problems and shortcomings in the prior art, the present invention provides a UV curing liquid and a preparation method and application thereof. The UV curing liquid introduces modified polyether polyols with long-chain structures, terminal hydroxyl polyolefins and fluorocarbon alcohol monomers, which can effectively improve the stain resistance and acid and alkali resistance of the cured film formed by the UV curing liquid, and can further improve the protective effect on the surface of related products such as electronic products.

[0006] According to the first aspect of the present invention, there is provided a UV curing liquid, comprising a main agent and a photoinitiator; the main agent comprises the following raw materials in parts by weight: 5-15 parts of modified polyether polyol or modified polyester polyol, 5-10 parts of terminal hydroxyl polyolefin, and 0.25-0.35 parts of fluorocarbon alcohol monomer; the modified polyether polyol or modified polyester polyol contains at least one of a cardanol structural unit and a cardanol diphenol structural unit.

[0007] The present invention effectively improves the anti-fouling effect and acid and alkali resistance of the cured film formed by the UV curing liquid by introducing a variety of materials such as cardanol, cardanol diphenol modified polyether polyol or modified polyester polyol, terminal hydroxyl polyolefin, and fluorocarbon alcohol monomer. At the same time, the hardness of the cured film is further improved, the overall performance of the cured film is optimized, and the protective effect of the cured film on the surface of related products such as electronic products is effectively enhanced.

[0008] First, cardanol, cardanol diphenol modified polyether polyol or modified polyester polyol, terminal hydroxyl polyolefin all have long chain structures, and all have good acid and alkali resistance. Moreover, this long chain structure can give the UV resin molecular chain mobility after curing, which can improve the overall flexibility of the resin, improve its impact resistance, and further improve the overall performance of the resin. In addition, cardanol modified polyether polyol has a benzene ring structure, which can further improve the rigidity of the resin and enhance its adhesion to the substrate, and optimize the resin's acid and alkali resistance and adhesion performance.

[0009] Secondly, cardanol, cardanol diphenol modified polyether polyol or modified polyester polyol, terminal hydroxyl polyolefin, fluorocarbon alcohol monomer contains polar groups such as hydroxyl groups, which can form chemical bonds, hydrogen bonds or van der Waals forces with the surface of the adherend, and thus have a synergistic effect in improving the adhesion of UV resin to the substrate, so that a variety of interactive forces are formed between the resin and the substrate, including chemical bonds, hydrogen bonds, van der Waals forces, etc., thereby greatly enhancing the adhesion of the resin to substrates of different materials, ensuring that the UV resin can be firmly attached to the surface of the adherend during use. Moreover, the hydroxyl groups contained in these three substances are active groups, which can participate in the curing reaction of UV resin, provide more additional active sites for the formation of cross-linked networks, enhance the complexity and stability of the network, and thus improve the rigidity and strength of the network, and improve the acid and alkali resistance of the cured resin.

[0010] Third, in the fluorocarbon alcohol monomer, the electronegativity of the fluorine atom is strong, so the fluorine atoms in the fluororesin molecules tend to stay away from other atoms, and form a relatively sparse structure on the surface of the molecular chain. This structure leads to a low surface energy of the fluorine-containing resin, which is not easily adsorbed by water or other liquids, thus giving the resin excellent anti-fouling properties. Moreover, the fluorocarbon alcohol monomer can participate in the reaction of the resin and be grafted into the resin molecule, avoiding the problem of precipitation and stratification that will easily occur over time after adding an appropriate amount of leveling agent (a small molecule containing a fluorine element) to the main resin, thereby further improving the cohesive strength of the resin and improving the acid and alkali resistance of the resin. Moreover, the fluorocarbon bond in the fluorocarbon alcohol has a high chemical stability and can effectively resist the erosion of chemical substances such as acids, bases, salts, and organic solvents. Therefore, the introduction of the fluorocarbon alcohol monomer can enhance the chemical corrosion resistance of the UV resin, so that the resin can still maintain good performance in some harsh chemical environments.

[0011] In addition, the three substances of cardanol, cardanol-modified polyether polyol or modified polyester polyol, terminal hydroxyl polyolefin, and fluorocarbon alcohol monomer can further cooperate with each other, especially the three can form a good mixed system, which further enables the UV resin to form a more uniform, dense and flexible cross-linked network structure, thereby improving the comprehensive performance of the resin. Moreover, these three substances can produce a certain synergistic effect, which can further improve the mechanical properties and acid and alkali resistance of the resin, and at the same time, this synergistic effect will not significantly affect the surface antifouling performance of the resin and the adhesion to the substrate.

[0012] Preferably, the modified polyether polyol or modified polyester polyol comprises at least one of cardanol polyether polyol and cashew nut shell oil polyester diol.

[0013] Preferably, the modified polyether polyol or modified polyester polyol comprises cardanol polyether polyol.

[0014] Preferably, the fluorocarbon alcohol monomer includes at least one of 2-perfluorobutylethyl alcohol, 2-perfluorohexylethyl alcohol, and 2-perfluorooctylethyl alcohol.

[0015] Preferably, the fluorocarbon alcohol monomer includes 2-perfluorobutyl ethyl alcohol. The introduction of the fluorocarbon alcohol monomer has a more obvious effect on the overall performance optimization of the UV resin, especially in terms of stain resistance and acid and alkali resistance.

[0016] Preferably, in the main agent, the mass proportion of fluorine in the solute is 0.30-0.40wt%. Here, it means that the mass proportion of fluorine in the main agent other than the solvent (i.e., the sum of other materials other than the solvent) is 0.30-0.40wt%. Controlling the mass proportion of fluorine in the solute is beneficial to taking into account the surface properties (fouling resistance), mechanical properties, acid and alkali resistance, and resin uniformity of the resin. If there is too little fluorine, the improvement effect on the antifouling performance, acid and alkali resistance, hardness and other properties of the resin is not good; if there is too much fluorine, because the fluorocarbon alcohol monomer has a relatively low polarity after all, the compatibility with the main resin is relatively poor, adding too much can easily cause uneven mixing of the glue, turbidity or even stratification, which is not conducive to forming a uniform and stable cross-linked network, and deteriorating the overall performance of the resin.

[0017] Preferably, the hydroxyl value of the cardanol-modified polyether polyol is 75-98 mgKOH / g; the hydroxyl value of the hydroxyl-terminated polyolefin is 60-200 mgKOH / g. Ensuring that the hydroxyl values ​​of the cardanol-modified polyether polyol and the hydroxyl-terminated polyolefin are within the above range is conducive to ensuring that the mixed system has a certain reactivity, improving the curing efficiency, and promoting the uniform mixing of the components, thereby improving the various properties of the resin. If the hydroxyl value is too high and the reactivity is too strong, the curing reaction may be too fast, generating a large amount of heat, causing problems such as uneven shrinkage of the resin and increased internal stress, affecting the curing quality, and thus affecting the overall performance of the resin.

[0018] Preferably, the average molecular weight of the hydroxyl-terminated polyolefin is 500-2000 g / mol. Controlling the average molecular weight of the hydroxyl-terminated polyolefin within the above range is conducive to making the resin have a suitable molecular weight and a good molecular weight distribution, controlling the crosslinking degree before curing, making the hardness of the final cured resin moderate, and optimizing the overall performance of the resin.

[0019] Preferably, the hydroxyl-terminated polyolefin includes hydroxyl-terminated polybutadiene (HTPB), hydroxyl-terminated hydrogenated polybutadiene (HLBH), hydroxyl-terminated butadiene styrene liquid rubber (HTBS), and hydroxyl-terminated polyisoprene (HTPI).

[0020] Preferably, the hydroxyl-terminated polyolefin comprises hydroxyl-terminated polybutadiene.

[0021] Preferably, the main agent also includes the following raw materials in parts by weight: 5-7.5 parts of active diluent, 5-10 parts of hydroxyl acrylic monomer; the active diluent contains hydroxyl. Furthermore, the above two materials containing active groups such as hydroxyl are introduced into the main agent, which is conducive to providing more active sites, further improving the density and structural stability of the cross-linked network, optimizing the internal cohesive strength of the resin, and thus further improving the hardness and acid and alkali corrosion resistance of the resin. At the same time, the active diluent can help regulate the overall viscosity of the glue, promote the full dissolution of each material, improve the overall uniformity of the material, and help the cured film to be more uniform and smooth.

[0022] Preferably, the reactive diluent includes a hydroxyl-containing multifunctional acrylate, and specifically, may include at least one of dipentaerythritol pentaacrylate and pentaerythritol triacrylate.

[0023] Preferably, the reactive diluent comprises pentaerythritol triacrylate.

[0024] Preferably, the hydroxy acrylic monomer includes at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate.

[0025] Preferably, the main agent also includes the following raw materials in parts by weight: 0.5-2.0 parts of chain extender, 10-25 parts of polyisocyanate. Further matching with appropriate chain extender and polyisocyanate can increase the molecular chain length, while improving the crosslinking density of the resin, thereby improving the cohesive strength of the resin, thereby further improving the hardness and acid and alkali resistance of the resin. In addition, polyisocyanate is conducive to improving the yellowing resistance of the resin and optimizing the overall performance of the resin.

[0026] Preferably, the main agent also includes the following raw materials in parts by weight: 0.0025-0.005 parts of catalyst.

[0027] Preferably, the chain extender includes at least one of ethylene glycol, butanediol and diethylene glycol.

[0028] Preferably, the catalyst comprises at least one of bismuth carboxylate, organic mercury, organic tin, and organic zinc.

[0029] Preferably, the polyisocyanate comprises an aliphatic type polyisocyanate.

[0030] Preferably, the aliphatic polyisocyanate includes at least one of hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, HDI trimer, HDI biuret, and IPDI trimer.

[0031] Preferably, the main agent further comprises the following raw materials in parts by weight: 30 to 80 parts of a first organic solvent.

[0032] Preferably, the first organic solvent includes at least one of dimethylformamide, toluene, butanone, and ethyl acetate.

[0033] Preferably, the first organic solvent is identical to the second organic solvent.

[0034] Preferably, the photoinitiator includes at least one of 1-hydroxy-cyclohexyl-phenyl ketone (184), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (907), and benzoin dimethyl ether (BDK).

[0035] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned UV curing solution, comprising the following steps: S1. uniformly mixing a modified polyether polyol, a terminal hydroxyl polyolefin, a chain extender and a first part of a first organic solvent, and heating the mixture to 50-60°C for reaction for 10-20 minutes to obtain a first mixed system; S2. adding polyisocyanate to the first mixed system, uniformly mixing the mixture, and heating the mixture to 80-90°C for reaction for 2-3 hours to obtain a second mixed system; S3. when the mass content of isocyanate groups in the second mixed system is equal to 4.5-5.5%, cooling the mixture to 65-75°C, adding a catalyst, pentaerythritol trimethylolpropane and a mixture of the second part of the first organic solvent, and maintaining the mixture at 40°C for 1 hour; React at 65-75°C for 0.5-1h to obtain a third mixed system; S4. Add a mixed solution of hydroxy acrylic monomer and the third part of the first organic solvent to the third mixed system, keep the temperature at 65-75°C and continue the reaction for 0.5-1h to obtain a fourth mixed system, S5. Add a mixed solution of fluorocarbon alcohol monomer and the fourth part of the first organic solvent to the fourth mixed system, keep the temperature at 65-75°C and continue the reaction for 0.5-1h to obtain a fifth mixed system; S6. After the isocyanate groups in the fifth mixed system are completely consumed, add the fifth part of the first organic solvent thereto, cool it down, and obtain a main agent; S7. Evenly mix the main agent, photoinitiator and second organic solvent to obtain a UV curing solution.

[0036] The above preparation method is advantageous for obtaining UV curing liquid with suitable molecular weight and good molecular weight distribution, so that the UV curing film prepared by the UV curing liquid also has a suitable molecular weight and good molecular weight distribution, which is advantageous for taking into account the mechanical properties (such as hardness), antifouling performance, and acid and alkali resistance of the resin, so that these properties are at a higher level. Among them, in S3, when the content of isocyanate groups in the second mixed system is equal to 4.5-5.5%, the catalyst and pentaerythritol trimethylolpropane are further added, which is to enable the subsequent reactive substances pentaerythritol trimethylolpropane and hydroxy acrylic acid monomer to be grafted, and the content of isocyanate groups is guaranteed to be 4.5-5.5%, so as to ensure that the prepolymer body forms a certain molecular weight, and can graft an appropriate amount of active acrylic acid monomer or other active substances, promote the full mixing of the components of the UV curing liquid, so that after UV, it is further cured to obtain a resin with a high cross-linking density, optimize the structural strength of the resin, and then optimize the hardness, antifouling performance and acid and alkali resistance of the resin. At the same time, the fluorocarbon alcohol monomer in S5 is connected to the end of the polymer, which can not only optimize the surface anti-fouling performance of the resin to the greatest extent, but also avoid the problem of precipitation and stratification that will easily occur over time after adding an appropriate amount of leveling agent (small molecules containing fluorine elements) to the main resin as in the past. This further improves the cohesive strength of the resin, and improves the acid and alkali resistance and other properties of the resin.

[0037] Preferably, the second organic solvent includes at least one of dimethylformamide, toluene, butanone, and ethyl acetate.

[0038] Preferably, the first organic solvent is identical to the second organic solvent.

[0039] Preferably, in S3, the catalyst, pentaerythritol trimethylolpropane and the mixed solution of the second part of the organic solvent are added dropwise. Preferably, in S3, the catalyst, pentaerythritol trimethylolpropane and the mixed solution of the second part of the organic solvent are added dropwise, and the dropping time does not exceed 2 hours. Preferably, the dropping time is 1-1.5 hours. The dropping method is more conducive to controlling the progress of the polymerization reaction and obtaining a resin with a suitable molecular weight and a good molecular weight distribution.

[0040] Preferably, in S4, the mixture of the hydroxy acrylic acid monomer and the third part of the organic solvent is added dropwise. Preferably, in S4, the mixture of the hydroxy acrylic acid monomer and the third part of the organic solvent is added dropwise, and the dropping time does not exceed 2 hours. Preferably, the dropping time is 1.5-2 hours. The dropping method is more conducive to controlling the progress of the polymerization reaction and obtaining a resin with a suitable molecular weight and a good molecular weight distribution.

[0041] Preferably, in S5, the mixed solution of the fluorocarbon alcohol monomer and the fourth part of the organic solvent is added in one go.

[0042] According to a second aspect of the present invention, there is provided a cured film obtained by curing the UV curing solution or the UV curing solution prepared by the method for preparing the UV curing solution.

[0043] According to a third aspect of the present invention, a polymer film is provided, comprising the above-mentioned UV curing liquid or a cured film obtained by curing the UV curing liquid prepared by the preparation method of the above-mentioned UV curing liquid, or the above-mentioned cured film. The above-mentioned UV curing liquid can be cured on the polymer film to form a uniform UV curing film with high cross-linking density and strong structural stability, and the film has good adhesion to the surface of the polymer film and has low surface properties, so it can play a good protective role on the surface of the polymer film.

[0044] Preferably, the material of the polymer film includes at least one of PET, PC, PVC, ABS, PE, PP, and BOPP.

[0045] Preferably, the material of the polymer film includes PET. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0047] Example 1

[0048] The UV curing liquid prepared in this embodiment includes a main agent and a photoinitiator accounting for 1.0 wt% of the total mass of the main agent, and the photoinitiator is 184.

[0049] (1) The raw materials are as follows:

[0050] Cardanol-modified polyether polyol: 9.34 parts of cardanol-modified polyether polyol (NX-9203) having a hydroxyl value of 98 mgKOH / g;

[0051] Hydroxyl-terminated polyolefin: 6.04 parts of hydroxyl-terminated polybutadiene (R-20LM) having a hydroxyl value of 101 mgKOH / g;

[0052] Catalyst: 0.003 parts of K-KAT348 bismuth carboxylate;

[0053] Chain extender: diethylene glycol (DEG) 1.44 parts;

[0054] Polyisocyanate: HDI biuret 19.87 parts;

[0055] Reactive diluent: 5.67 parts of pentaerythritol triacrylate (PET3A);

[0056] Hydroxylated acrylic monomer: 7.23 parts of hydroxyethyl methacrylate (HEMA);

[0057] Fluorocarbon alcohol monomer: 0.28 parts of 2-perfluorobutyl ethyl alcohol (DAIKINA-1420);

[0058] The first organic solvent: 50 parts of ethyl acetate;

[0059] Second organic solvent: ethyl acetate, added as needed.

[0060] (2) The preparation method is as follows:

[0061] S1. Mix NX-9203, R-20LM, DEG and 10 parts of ethyl acetate, heat to 50-60°C, and stir for 10-20 minutes to obtain a first mixed system;

[0062] S2. To the first mixed system, HDI biuret was added and the temperature was raised to 80-90 ° C and refluxed for 2-3h to obtain a second mixed system;

[0063] S3. When the content of isocyanate groups in the second mixed system is ≤4.89%, the temperature is lowered to 65-75°C, and a mixture of K-KAT348, PET3A and 12.5 parts of ethyl acetate is added dropwise within 1-1.5 hours, and the reaction temperature is maintained at 65-75°C. The reaction is carried out for 0.5-1h to obtain a third mixed system;

[0064] S4. HEMA and 12.5 parts of ethyl acetate were added dropwise to the third mixed system, the titration time was 1.5-2.0h, the reaction temperature was maintained at 65-75°C, and the reaction was continued for 0.5-1h to obtain a fourth mixed system;

[0065] S5. DAIKINA-1420 and 10 parts of ethyl acetate were added to the fourth mixed system at one time, the reaction temperature was maintained at 65-75 ° C, and the reaction was continued for 0.5-1h to obtain a fifth mixed system;

[0066] S6. After the isocyanate group of the fifth mixed system is completely consumed, 5 parts of ethyl acetate are added and the temperature is lowered to obtain the main agent;

[0067] S7. dilute the main agent and the photoinitiator in the remaining ethyl acetate to obtain a UV curing solution. Specifically, dilute the main agent and the photoinitiator in ethyl acetate to a solute mass fraction of 35 wt % to obtain a UV curing solution.

[0068] (3) Preparation of UV curable film

[0069] Apply the above UV curing liquid on 50μm corona PET and control the glue amount to 3-5g / m 2 After coating, place it in a 110℃ oven for 45 seconds. The curing conditions are: 365-395nm wavelength LED lamp curing for 15 seconds.

[0070] Example 2

[0071] The UV curing liquid prepared in this embodiment includes a main agent and a photoinitiator accounting for 1.0 wt% of the total mass of the main agent, and the photoinitiator is 184.

[0072] (1) The raw materials are as follows:

[0073] Cardanol-modified polyether polyol: 9.00 parts of cardanol-modified polyether polyol (NX-9203) having a hydroxyl value of 98 mgKOH / g;

[0074] Hydroxyl-terminated polyolefin: 5.82 parts of hydroxyl-terminated polybutadiene (R-20LM) having a hydroxyl value of 101 mgKOH / g;

[0075] Catalyst: 0.003 parts of K-KAT348 bismuth carboxylate;

[0076] Chain extender: diethylene glycol (DEG) 1.39 parts;

[0077] Polyisocyanate: HDI trimer 20.20 parts;

[0078] Reactive diluent: 5.47 parts of pentaerythritol triacrylate (PET3A);

[0079] Hydroxylated acrylic monomer: 7.72 parts of hydroxypropyl methacrylate (HPMA);

[0080] Fluorocarbon alcohol monomer: 0.25 parts of 2-perfluorobutyl ethyl alcohol (DAIKINA-1420);

[0081] The first organic solvent: 50 parts of ethyl acetate;

[0082] Second organic solvent: ethyl acetate, added as needed.

[0083] (2) The preparation method of UV curing solution is the same as that in Example 1.

[0084] (3) The preparation of UV curable adhesive film is the same as that in Example 1.

[0085] Example 3

[0086] The UV curing liquid prepared in this embodiment includes a main agent and a photoinitiator accounting for 1.0 wt% of the total mass of the main agent, and the photoinitiator is 184.

[0087] (1) The raw materials are as follows:

[0088] Cardanol-modified polyether polyol: 6.84 parts of cardanol-modified polyether polyol (NX-9203) having a hydroxyl value of 98 mgKOH / g;

[0089] Hydroxyl-terminated polyolefin: 5.43 parts of hydroxyl-terminated polybutadiene (R-20LM) having a hydroxyl value of 101 mgKOH / g;

[0090] Catalyst: 0.0025 parts of K-KAT348 bismuth carboxylate;

[0091] Chain extender: butanediol (BDO) 0.98 parts;

[0092] Polyisocyanate: 24.25 parts of IPDI trimer;

[0093] Reactive diluent: 5.66 parts of pentaerythritol triacrylate (PET3A);

[0094] Hydroxylated acrylic monomer: 6.44 parts of hydroxyethyl acrylate (HEA);

[0095] Fluorocarbon alcohol monomer: 0.26 parts of 2-perfluorobutyl ethyl alcohol (DAIKINA-1420);

[0096] The first organic solvent: 50 parts of ethyl acetate;

[0097] Second organic solvent: ethyl acetate, added as needed.

[0098] (2) The preparation method of UV curing solution is the same as that in Example 1.

[0099] (3) The preparation of UV curable adhesive film is the same as that in Example 1.

[0100] Example 4

[0101] The UV curing liquid prepared in this embodiment includes a main agent and a photoinitiator accounting for 1.0 wt% of the total mass of the main agent, and the photoinitiator is 184.

[0102] (1) The raw materials are as follows:

[0103] Cardanol-modified polyether polyol: 12.38 parts of cardanol-modified polyether polyol (NX-9203) having a hydroxyl value of 98 mgKOH / g;

[0104] Hydroxyl-terminated polyolefin: 8.01 parts of hydroxyl-terminated polybutadiene (R-20LM) having a hydroxyl value of 101 mgKOH / g;

[0105] Catalyst: K-KAT348 bismuth carboxylate 0.0041 parts;

[0106] Chain extender: 1.12 parts of ethylene glycol (EG);

[0107] Polyisocyanate: IPDI 14.00 parts;

[0108] Reactive diluent: 6.18 parts of pentaerythritol triacrylate (PET3A);

[0109] Hydroxylated acrylic acid monomer: 7.87 parts of hydroxypropyl acrylate (HPA);

[0110] Fluorocarbon alcohol monomer: 0.26 parts of 2-perfluorobutyl ethyl alcohol (DAIKINA-1420);

[0111] The first organic solvent: 50 parts of ethyl acetate;

[0112] Second organic solvent: ethyl acetate, added as needed.

[0113] (2) The preparation method of UV curing solution is the same as that in Example 1.

[0114] (3) The preparation of UV curable adhesive film is the same as that in Example 1.

[0115] Example 5

[0116] The difference between this embodiment and embodiment 1 is that the raw material fluorocarbon alcohol monomer is adjusted to 2-perfluorobutyl ethyl alcohol. The rest is the same as embodiment 1.

[0117] Example 6

[0118] The difference between this embodiment and embodiment 1 is that the raw material fluorocarbon alcohol monomer is adjusted to a mixture of 2-perfluorobutyl ethyl alcohol and 2-perfluorooctyl ethyl alcohol, and the mass ratio of 2-perfluorobutyl ethyl alcohol to 2-perfluorooctyl ethyl alcohol is 1:1, and the total mass of the fluorocarbon alcohol monomer remains unchanged. The rest is the same as embodiment 1.

[0119] Example 7

[0120] The difference between this embodiment and embodiment 1 is that the mass fraction of 2-perfluorobutyl ethyl alcohol in the raw material fluorocarbon alcohol monomer is adjusted to 0.32 parts, so that the mass proportion of fluorine element in the solute is 0.415wt%. The rest is the same as embodiment 1.

[0121] Example 8

[0122] The difference between this embodiment and embodiment 1 is that the mass fraction of 2-perfluorobutylethyl alcohol in the raw material fluorocarbon alcohol monomer is adjusted to 0.14, so that the mass fraction of fluorine element in the solute is 0.182wt%. The rest is the same as embodiment 1.

[0123] Example 9

[0124] The difference between this embodiment and embodiment 1 is that the raw material cardanol-modified polyether polyol is adjusted to NX-9201LP cashew nut shell oil polyester diol with a hydroxyl value of 70 mgKOH / g. The rest is the same as embodiment 1.

[0125] Example 10

[0126] The difference between this embodiment and embodiment 1 is that the hydroxyl value of the raw material terminal hydroxyl polybutadiene is 40 mgKOH / g. The rest is the same as embodiment 1.

[0127] Embodiment 11

[0128] The difference between this embodiment and embodiment 1 is that pentaerythritol triacrylate is adjusted to dipentaerythritol pentaacrylate, and the amount is adjusted to 9.89 parts. The rest is the same as embodiment 1.

[0129] Example 12

[0130] The difference between this embodiment and embodiment 1 is that the amount of hydroxyethyl methacrylate (HEMA) in the raw material hydroxy acrylic acid monomer is adjusted to 12 parts. The rest is the same as embodiment 1.

[0131] Example 13

[0132] The difference between this embodiment and the first embodiment is that, in the process of preparing the UV curing solution, in S3, the content of isocyanate groups in the second mixed system is controlled to be equal to 4% before the temperature is lowered. The rest is the same as the first embodiment.

[0133] Comparative Example 1

[0134] The UV curing liquid prepared in this comparative example includes a main agent and a photoinitiator accounting for 1.0 wt% of the total mass of the main agent, and the photoinitiator is 184.

[0135] (1) The raw materials are as follows:

[0136] Hydroxyl-terminated polyolefin: 13.63 parts of hydroxyl-terminated polybutadiene (R-20LM) having a hydroxyl value of 101 mgKOH / g;

[0137] Catalyst: K-KAT348 bismuth carboxylate 0.0027 parts;

[0138] Chain extender: diethylene glycol (DEG) 1.30 parts;

[0139] Polyisocyanate: HDI biuret 17.92 parts;

[0140] Reactive diluent: 7.31 parts of pentaerythritol triacrylate (PET3A);

[0141] Hydroxylated acrylic monomer: 9.31 parts of hydroxyethyl methacrylate (HEMA);

[0142] Fluorocarbon alcohol monomer: 0.32 parts of 2-perfluorobutyl ethyl alcohol (DAIKINA-1420);

[0143] The first organic solvent: 50 parts of ethyl acetate;

[0144] Second organic solvent: ethyl acetate, added as needed.

[0145] (2) The preparation method of UV curing solution is the same as that in Example 1.

[0146] (3) The preparation of UV curable adhesive film is the same as that in Example 1.

[0147] Comparative Example 2

[0148] The UV curing liquid prepared in this comparative example includes a main agent and a photoinitiator accounting for 1.0 wt% of the total mass of the main agent, and the photoinitiator is 184.

[0149] (1) The raw materials are as follows:

[0150] Cardanol-modified polyether polyol: 16.78 parts of cardanol-modified polyether polyol (NX-9203) having a hydroxyl value of 98 mgKOH / g;

[0151] Catalyst: 0.0034 parts of K-KAT348 bismuth carboxylate;

[0152] Chain extender: diethylene glycol (DEG) 1.55 parts;

[0153] Polyisocyanate: HDI biuret 21.42 parts;

[0154] Reactive diluent: 4.37 parts of pentaerythritol triacrylate (PET3A);

[0155] Hydroxylated acrylic monomer: 5.56 parts of hydroxyethyl methacrylate (HEMA);

[0156] Fluorocarbon alcohol monomer: 0.31 parts of 2-perfluorobutyl ethyl alcohol (DAIKINA-1420);

[0157] The first organic solvent: 50 parts of ethyl acetate;

[0158] Second organic solvent: ethyl acetate, added as needed.

[0159] (2) The preparation method of UV curing solution is the same as that in Example 1.

[0160] (3) The preparation of UV curable adhesive film is the same as that in Example 1.

[0161] Comparative Example 3

[0162] The difference between this comparative example and Example 1 is that, among the raw materials used, the cardanol-modified polyether polyol is adjusted to polyoxypropylene polyether polyol (PPG-1000) having a hydroxyl value of 112 mgKOH / g. The rest is the same as Example 1.

[0163] Comparative Example 4

[0164] The difference between this comparative example and Example 1 is that, among the raw materials used, the hydroxy-terminated polybutadiene is adjusted to polybutylene adipate polyester polyol (PBA-1000) having a hydroxyl value of 112 mgKOH / g. The rest is the same as Example 1.

[0165] Comparative Example 5

[0166] The difference between this comparative example and Example 1 is that the raw materials used do not contain fluorocarbon alcohol monomers, that is, do not contain 2-perfluorobutyl ethyl alcohol, that is, step S5 in the preparation method is not performed. The rest is the same as Example 1.

[0167] Comparative Example 6

[0168] The difference between this comparative example and Example 1 is that, in the raw materials used, the fluorocarbon alcohol monomer 2-perfluorobutyl ethyl alcohol is adjusted to perfluoro-2,5-dimethyl-3,6-dioxaoctanoic acid; and in the preparation method of the UV curing solution, step S5 is not performed, and in S7, the main agent, the photoinitiator and the above perfluoro-2,5-dimethyl-3,6-dioxaoctanoic acid are directly mixed to obtain the UV curing solution. The rest is the same as Example 1.

[0169] Test Case

[0170] 1. Experimental Construction Method

[0171] The products obtained in all the above embodiments and comparative example (3) were used as test objects and the following performance tests were performed:

[0172] a. Corona value test: First, clean the surface of the test object and lay it flat on a horizontal table. Use a corona pen to lightly draw a line on the surface where the primer layer of the test object is located. If the liquid does not shrink within three seconds, it reaches the dyne value selected by the corona pen, otherwise it does not reach it. The lower the corona value, the smaller the surface tension of the substrate and the better the surface antifouling ability.

[0173] b. Adhesion test: According to GB / T9286-1998, the coating is applied on the 50μm PET original film, and the coating thickness is controlled at 3-5g / m 2 , use a 1mm spacing grid knife to scrape out 100 small squares, stick M600 or 610 tape in the grids, quickly pull up the 3M tape, and test the number of pieces that fall off.

[0174] c. Pencil hardness test: According to GB / T6739-2006 "Determination of paint film hardness by pencil method for paints and varnishes", select a pencil of appropriate hardness for the prepared samples. If the paint film shows plastic deformation or cohesive failure during the test, use a pencil of lower hardness for testing until the paint film is no longer damaged after the pencil passes through it. Repeat 3 times. If the results are consistent, the pencil hardness is deemed to be equivalent to that of a pencil of that hardness.

[0175] d. Acid and alkali resistance test: Place the prepared paint film in 25% sulfuric acid and 25% NaOH solution respectively. After placing it at 80℃ for 1 day, wipe off the sulfuric acid or NaOH on the surface and conduct a pencil hardness test.

[0176] 2. Experimental results

[0177] The relevant properties of the UV curable adhesive films after being cured by the UV curing liquid of all the above embodiments and comparative examples are shown in Table 1 below.

[0178] Table 1 Relevant performance results of UV curable adhesive films after UV curing liquid curing of the embodiment and the comparative example

[0179]

[0180]

[0181] It should be noted here that the calculation method for the fluorine content in the above Table 1 is: fluorine content = [(relative atomic mass of fluorine element × number of atoms) / relative molecular mass of fluorine monomer] × mass of fluorine monomer / total amount of system (excluding solvent). For example, in Example 1, fluorine content = [(19×9) / 264×0.28] / (9.34+6.04+0.003+1.44+19.87+5.67+7.23+0.28) = 0.364%. The molecular formula of the fluorine monomer in Example 1 is C6H5F9O, and the molar mass is 264 g / mol.

[0182] As shown in Table 1, the long-chain cardanol-modified polyether polyol, hydroxyl-terminated polyolefin and fluorocarbon alcohol monomer introduced into the UV curing solution provided by the present invention can effectively improve the anti-fouling performance and acid-base resistance of the cured film formed by the UV curing solution, and can further improve the protective effect on the surface of related products such as electronic products. Specific reference is made to Examples 1 to 13.

[0183] In comparative example 1, no modified polyether polyol or modified polyester polyol is added; in comparative example 2, no hydroxyl-terminated polyolefin is added; in comparative example 3, the cardanol-modified polyether polyol in example 1 is changed to polyoxypropylene polyether polyol; in comparative example 4, the hydroxyl-terminated polybutadiene in example 1 is adjusted to polybutylene adipate polyester polyol; in comparative example 5, no fluorocarbon alcohol monomer is contained; in comparative example 6, the fluorocarbon alcohol monomer is a commonly used leveling agent, a small molecule perfluoro-2,5-dimethyl-3,6-dioxaoctanoic acid, which does not participate in the reaction and is directly mixed with other materials to obtain a UV curing liquid. The above factors cause the cured films in comparative examples 1 to 4 to have a significant decrease in adhesion or acid and alkali resistance, the antifouling ability of the cured film in comparative example 5 is significantly reduced, and the film in comparative example 6 is initially transparent, and gradually becomes foggy as time goes by, which no longer meets the standard that the cured film needs to be transparent, and loses the meaning of performance evaluation (the cured films of other embodiments and comparative examples are transparent). This shows that the combination of the modified polyether polyol or modified polyester polyol, the terminal hydroxyl polyolefin and the fluorocarbon alcohol monomer in the present invention is crucial for the cured film obtained by UV curing liquid to have multiple properties such as antifouling performance, adhesion, acid and alkali resistance.

[0184] Further comparing Example 1 with Examples 5 and 6, the fluorocarbon alcohol monomer in Example 5 is 2-perfluorohexylethyl alcohol, and the fluorocarbon alcohol monomer in Example 6 is 2-perfluorobutylethyl alcohol and 2-perfluorooctylethyl alcohol, and the corona values ​​of the cured films in Examples 5 and 6 are higher (poor antifouling performance), and the adhesion is also reduced. This shows that when the fluorocarbon alcohol monomer is 2-perfluorohexylethyl alcohol, it is more conducive to optimizing the antifouling performance and adhesion of the cured film formed after UV curing liquid is cured, and further improving the comprehensive performance of the cured film.

[0185] Comparing Example 1 with Examples 7 and 8, the contents of the fluorocarbon alcohol monomer 2-perfluorobutylethyl alcohol in Examples 7 and 8 are respectively too much and too little (the fluorine content is respectively too much and too little), resulting in a decrease in the adhesion of the cured film in Example 7 and an increase in the corona value of the cured film in Example 8, that is, the anti-fouling ability is deteriorated. This shows that further controlling the fluorine content within a specific range is beneficial to taking into account both the adhesion and anti-fouling ability of the cured film, that is, it is more conducive to improving the overall performance of the cured film.

[0186] Comparing Example 1 with Examples 9 and 10, Example 9 uses cashew nut shell oil polyester diol with a relatively low hydroxyl value, and Example 10 uses terminal hydroxyl polybutadiene with a low hydroxyl value, which causes the adhesion of the cured films in Examples 9 and 10 to decrease. Therefore, it is necessary to ensure that the hydroxyl value is within a certain range, which is more conducive to improving the overall performance of the cured film.

[0187] Comparing Example 1 with Examples 11 and 12, the type of active diluent in Example 11 is dipentaerythritol pentaacrylate, and the proportion of hydroxyethyl methacrylate, a hydroxyacrylic acid monomer, in Example 12 is relatively high, resulting in decreased adhesion and acid and alkali resistance of the cured film in Example 11, and decreased alkali resistance of the cured film in Example 12. This indicates that it is necessary to select a suitable active diluent and control the amount of the hydroxyacrylic acid monomer within a specific range, which is more conducive to taking into account various aspects of the performance of the cured film.

[0188] Comparing Example 1 and Example 13, in S3 of Example 13, the content of isocyanate groups in the second mixed system is controlled to be equal to 3% and then the temperature is lowered, resulting in insufficient isocyanate groups to react with the active diluent and the hydroxyl group of the hydroxyl acrylic monomer, resulting in a significant decrease in the adhesion performance of the cured film obtained after the UV curing liquid is cured.

[0189] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A UV curing solution, characterized in that: Including main agent and photoinitiator; The main agent comprises the following raw materials in parts by weight: 5-15 parts of modified polyether polyol or modified polyester polyol, 5-10 parts of terminal hydroxyl polyolefin, and 0.25-0.35 parts of fluorocarbon alcohol monomer; The modified polyether polyol or the modified polyester polyol contains at least one of a cardanol structural unit and a cardanol diphenol structural unit.

2. The UV curing solution according to claim 1, characterized in that: The fluorocarbon alcohol monomer includes at least one of 2-perfluorobutyl ethyl alcohol, 2-perfluorohexyl ethyl alcohol, and 2-perfluorooctyl ethyl alcohol.

3. The UV curing solution according to claim 1, characterized in that: In the main agent, the mass proportion of fluorine element in the solute is 0.30-0.40wt%.

4. The UV curing solution according to claim 1, characterized in that: The cardanol-modified polyether polyol has a hydroxyl value of 70-98 mgKOH / g; The hydroxyl value of the hydroxyl-terminated polyolefin is 60-200 mgKOH / g.

5. The UV curing solution according to claim 1, characterized in that: The average molecular weight of the hydroxyl-terminated polyolefin is 500-2000 g / mol.

6. The UV curing solution according to claim 1, characterized in that: The main agent also includes the following raw materials in parts by weight: 5-7.5 parts of active diluent and 5-10 parts of hydroxy acrylic acid monomer; the active diluent contains hydroxyl group.

7. The UV curing solution according to claim 1, characterized in that: The main agent also includes the following raw materials in parts by weight: 0.5-2.0 parts of chain extender and 10-25 parts of polyisocyanate.

8. A method for preparing the UV curing solution according to any one of claims 1 to 7, characterized in that: The steps include: S1. The modified polyether polyol, the hydroxyl-terminated polyolefin, the chain extender and the first part of the first organic solvent are mixed uniformly, and the temperature is raised to 50-60° C. and reacted for 10-20 min to obtain a first mixed system; S2. Add polyisocyanate to the first mixed system and mix well, and heat to 80-90 ° C for 2-3h to obtain a second mixed system; S3. When the mass content of isocyanate groups in the second mixed system is equal to 4.5-5.5%, the temperature is lowered to 65-75 ° C, a catalyst, pentaerythritol trimethylolpropane and a mixture of the second part of the first organic solvent are added thereto, and the reaction is maintained at 65-75 ° C for 0.5-1h to obtain a third mixed system; S4. Add the hydroxy acrylic acid monomer and the third part of the first organic solvent to the third mixed system, and continue the reaction at 65-75° C. for 0.5-1 h to obtain a fourth mixed system. S5. Adding the fluorocarbon alcohol monomer and the fourth part of the first organic solvent mixture to the fourth mixed system, maintaining the reaction at 65-75 ° C for 0.5-1h to obtain a fifth mixed system; S6. After the isocyanate groups in the fifth mixed system are completely consumed, adding the fifth portion of the first organic solvent thereto, cooling, to obtain the main agent; S7. Evenly mix the main agent, the photoinitiator and the second organic solvent to obtain the UV curing solution.

9. A cured film, characterized in that: The UV curing liquid prepared by the UV curing liquid according to any one of claims 1 to 7 or the UV curing liquid preparation method according to claim 8 is cured.

10. A polymer film, characterized in that: It comprises the UV curing liquid according to any one of claims 1 to 7, or a cured film obtained by curing the UV curing liquid prepared by the preparation method of the UV curing liquid according to claim 8, or the cured film according to claim 9.

Citation Information

Patent Citations

  • Modified acrylate prepolymer, preparation method thereof and UV hardening liquid

    CN110606912A

  • High-wear-resistant fingerprint-resistant matte UV hardening liquid for composite plate, and preparation method of high-wear-resistant fingerprint-resistant matte UV hardening liquid

    CN112980318A

  • Method for preparing hydroxyl-terminated polybutadiene modified ultraviolet light curable waterborne polyurethane

    CN105482059A

  • UV-curable polyurethane acrylate photosensitive resin and its preparation method and use

    CN106977694A

  • Light-cured epoxy resin / polyurethane anticorrosive paint containing cardanol

    CN119264787A